2003
DOI: 10.1080/00365590310008677
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Varicocele on Testicular Artery Blood Flow in Men Color Doppler Investigation

Abstract: Testicular arterial blood flow was found to be significantly decreased in men with varicocele. This may be a reflection of the impaired microcirculation. Following decreased testicular arterial blood flow, impaired spermatogenesis may result from defective energy metabolism in the microcirculatory bed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 35 publications
5
49
0
5
Order By: Relevance
“…These TA's variations have been estimated in an incidence of 4.7-20% [5,22,24,40]. These aberrancies display significance from a clinical viewpoint since the TA's blood flow was found to be significantly decreased in men with varicocele [46]. Although many cases of double TAs have been documented in the literature [7,11,32,47], the bilateral presence of double TAs is more rarely detected [22,37].…”
Section: Introductionmentioning
confidence: 99%
“…These TA's variations have been estimated in an incidence of 4.7-20% [5,22,24,40]. These aberrancies display significance from a clinical viewpoint since the TA's blood flow was found to be significantly decreased in men with varicocele [46]. Although many cases of double TAs have been documented in the literature [7,11,32,47], the bilateral presence of double TAs is more rarely detected [22,37].…”
Section: Introductionmentioning
confidence: 99%
“…Testicular tissue is very sensitive to disruption of its nutritive supply, which is primarily via the hematogenous route. Several investigations in humans [1][2][3][4] and rats [5,6] have demonstrated an association between testicular blood flow and sperm quality. In addition to local mediators, hormones appear to be involved in regulation of testicular blood flow [6].…”
mentioning
confidence: 99%
“…It is suggested that hormonal or neuronal factors might be important. Contrary to this, some studies reported that varicocele never altered testicular blood flow or caused a decrease in blood flow (18,19).…”
Section: Discussionmentioning
confidence: 82%